The Statutes at Large of Pennsylvania from 1682 to 1801, at, 46-49, ch. 456, §§ 1-8 - (:unkn) unknown (General Publisher, 1721)
That if any person or persons shall presume, at any time after the sixteenth day of November, in this present year on thousand seven hundred and twenty one, to carry any gun or hunt on the improved or inclosed lands of any plantation other than his own, unless he have license or permission from the owner of such lands or plantation, and shall thereof convicted ether upon view of any justice of the peace within this province, or by the oath or affirmation of any one or more witnesses, before any justice of the peace, he shall for every such offense forfeit the sum of ten shillings.
--
Keywords: HUNTING REGULATION